Desenvolvimento de suplemento nitrogenado revestido com ceras - Alexandre Guimarães Inácio (2022)
The use of protein supplementation can speed up weight gain, especially for ruminants kept on pastures during the dry season, making this production more efficient. Urea is one of the main supplement used in these cases due to its low cost, good availability and practical use. However, as it is hygroscopic and quickly converted into ammonia in an aqueous medium, the use must be cautious. Cases of urea intoxication are not unusual and can lead the animals to death. Aiming to get around this problem, controlled-release urea (protected/coated) has been studied and commercially used for years. One of the factors that can limit the nutritional efficiency of this type of product is the requirement for ready availability of carbohydrates, necessary for protein synthesis along with the nitrogen provided by urea (synchronization). Thus, the present work aimed to develop and evaluate different supplements composed of urea and carbohydrates, coated with wax, aiming at a better synchronization of these nutrients in the rumen environment and a better efficiency in their use. The developed supplements and two other commercial products based on extruded urea (EU) and polymer coated urea (UP) were tested for solubility, thermal analysis, microscopic analysis, chemical analysis and cumulative gas production. The waxes used in the coating process proved to be efficient in reducing urea solubilization. The accumulated production of gas presented greater production in relation to the product named “F17”. Through thermogravimetric analysis, it was possible to verify the chemical integrity of the ingredients that make up the developed supplements. It has been found that it is possible to reduce the solubility of urea by using carnauba wax as a coating material. The formula with cassava starch (F17) associated with urea showed better synchronization during the degradability of the components.